KORELASI TINGKAT PENDIDIKAN DENGAN TINGKAT PENGETAHUAN TENTANG MENYIKAT GIGI PADA IBU PKK ASRAMA TNI YANG BATU DENPASAR TAHUN 2020 - I Gusti Ayu Agung Putu Swastini; I Gusti Agung Ayu Dharmawati; Sagung Agung Putri Dwiastuti; I G A Raiyanti; Siti Fatimah (Jurnal Kesehatan Gigi (Dental Health Journal), 2021)
Oral health is closely related to behavior. A person's behavior is influenced by knowledge, including knowledge of teeth brushing.  Teeth brushing is an action to clean teeth and mouth from food debris which aims to prevent disease in hard and soft tissues. The purpose of this study was to determine the level of knowledge of brushing the teeth of the PKK Indonesian Military Dormitory in Yang Batu Denpasar in 2020. This research is a descriptive study using a survey design. The sample in this study was the mother PKK TNI Dormitory Yang Batu Denpasar, totaling 60 respondents. The research data were analyzed using the Spearman correlation test. Based on the results of the study, the level of knowledge of brushing teeth showed that the percentage of PKK mothers who obtained a good level of knowledge was 19 people (31.67%), 36 people (60%) sufficient criteria and less as many as 5 people (8.33%). The average level of knowledge on brushing the teeth of PKK in the Yang Batu Military Dormitory was 72.16 with sufficient criteria. The conclusion of this research is that most of the PKK women of the TNI Yang Batu Dormitory have a sufficient level of knowledge.